Предмет: Алгебра,
автор: Агато4ка
Помогите решить.
Ответы
Автор ответа:
0
пусть t = x^2-4x+6
21/t+4 = t l * (t+4) не равное 0
значит, t не равно -4
21 = t^2 + 4t
t^2 + 4t - 21 = 0
D/4 = 4 + 21 = 25
t1 = -2 + 5 = 3
t2 = -2 - 5 = -7
21/t+4 = t l * (t+4) не равное 0
значит, t не равно -4
21 = t^2 + 4t
t^2 + 4t - 21 = 0
D/4 = 4 + 21 = 25
t1 = -2 + 5 = 3
t2 = -2 - 5 = -7
Похожие вопросы
Предмет: Математика,
автор: Аноним
Предмет: Русский язык,
автор: Falkai
Предмет: История,
автор: Varvaraprotasova
Предмет: Биология,
автор: Masha0575
Предмет: Биология,
автор: Александр2096